3(y-1)=y-11 plz solve this equation with explaination

Question

3(y-1)=y-11 plz solve this equation with explaination

in progress 0
Thiên Hương 7 months 2021-07-27T11:47:10+00:00 2 Answers 4 views 0

Answers ( )

    0
    2021-07-27T11:48:40+00:00

    Answer:

    -14

    Step-by-step explanation:

    3(y-1)=y-11

    3y-3=y-11

    y=3-11

    y= -14

    Multiply 3 into (y-1)

    Then substitute 3 for Y

    bringthe 3 over the equal sign to y

    3y-3 = -3-11

    y = -14

    0
    2021-07-27T11:48:45+00:00

    3(y-1)=y-11

    Distribute:
    3y – 1 = y- 11

    Add 11 to both sides

    3y – 12 = y

    subtract 3y on both sides

    -12 = -2y

    Divide by 2y

    y= 6

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )